Coastal Wetland Surface Elevation Change Is Dynamically Related to Accommodation Space and Influenced by Sedimentation and Sea-Level Rise Over Decadal Timescales - Rogers, Kerrylee; Zawadzki, Atun; Mogensen, Laura A.; Saintilan, Neil (Frontiers in Marine Science, 2022)
The fate of mangroves and saltmarshes under conditions of accelerating sea-level rise is dependent upon sedimentation and surface elevation gain that is sufficient to maintain substrate positions within a shifting tidal frame. This study focuses on coastal wetlands fringing Westernport Bay, a large tidal embayment of southeastern Australia where mangroves occupy lower tidal positions than saltmarshes. Estimates of vertical accretion, surface elevation change, and autocompaction derived from a 20-year record of observations were integrated with estimates of sedimentation at the decadal to century time-scale derived from 210Pb chronology to model the relationship between surface elevation gain and accommodation space at timescales relevant to management and decision-making. This model was validated against records of shoreline changes extracted from time-series aerial photography. Sedimentation and surface elevation gain vary spatially on the basis of available accommodation space and sediment supply, which are influenced by hydrodynamic conditions within the bay. Since sea-level rise increases available accommodation space, these relationships provided the means to project the outcome of accelerating sea-level rise on equilibrium accommodation space of mangroves and saltmarshes. Sea-level rise will generally deepen substrate positions within the tidal frame, creating conditions favorable for mangrove forests. Where sediment supply is high, maintenance (and some progradation) of mangrove shorelines may occur under projected low rates of sea-level rise; these conditions are limited to shorelines near sedimentary basins and where there is considerable lateral accommodation space. The same fate is not likely under a high sea-level rise scenario where shoreline retreat is projected in all settings. Given the limited accommodation space within saltmarshes at Westernport Bay, sedimentation will not be sufficient to maintain tidal positions and landward retreat will be critical for maintenance of saltmarsh biodiversity. This will require planning decisions to facilitate tidal incursions and conserve retreat pathways.